PLANT DISEASE RECOGNITION BASED ON PLANT LEAF IMAGE - S. W. Zhang Y. J. Shang; L. Wang (Journal of Animal and Plant Sciences, 2015)
Plant disease automatic detection is an important research topic as it has been proved useful in monitoring large crop fields, and thus automatically detects the leaf disease symptoms as soon as they appear in plant leaves. In this paper, a plant disease recognition method is proposed based on plant leaf images. First, the spot is segmented, and the disease feature vector is extracted. Then, the extracted features are provided for the K-nearest-neighbor classifier to recognize the plant diseases. Experimental results show the effectiveness of the proposed approach.
Keywords: Leaf image segmentation; Plant disease identification; Feature extraction